Atlas of Cardiac Innervation - Dilsizian, Vasken; Narula, Jagat (Springer International Publishing : Imprint: Springer, 2017)
This atlas elucidates the role of the neuronal component in normal cardiovascular function and cardiac disorders and discusses the currently available imaging targets and probes. It provides a foundation in cardiac neuronal imaging and image processing and serves as a guide in the effective utilization of these techniques in clinical and research settings. The atlas discusses the principles of autonomic control in the regulation of cardiac function and disease; chemistry and biology of radiotracers designed to target changes in the myocardial sympathetic and parasympathetic innervation as a function of disease or treatment; neuronal imaging in heart failure and reverse remodeling and the use of PET imaging in quantification of cardiac innervation; cardiac sympathetic innervation in ventricular arrhythmias and device therapy; conditions that affect the autonomic nervous system; and the role of myocardial blood flow and cardiac neuronal imaging in denervation and reinnervation in cardiac transplant recipients. Featuring full-color illustrations, schematic diagrams, and diagnostic algorithms, Atlas of Cardiac Innervation is a valuable resource for cardiologists, radiologists, nuclear medicine physicians, and electrophysiologists. .
Keywords: Medicine.; Radiology.; Nuclear medicine.; Cardiology.; elektronické knihy; electronic books